2020
DOI: 10.3389/fmed.2020.581336
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Ultrasound of Multiple Arterial Areas Reveals Increased Intima Media Thickness, Vessel Wall Appearance, and Atherosclerotic Plaques in Systemic Lupus Erythematosus

Abstract: Introduction: Despite improved therapies and management, patients with systemic lupus erythematosus (SLE) still have increased risks of cerebrovascular and cardiovascular disease. High-frequency ultrasound (US) provides an opportunity to distinguish atherosclerosis from inflammation in the vessels. We hypothesized that an extended US protocol may add information regarding vascular affection in SLE. Methods: Sixty patients (52 women, 8 men; mean age 43.2 ± 11.3 years) with SLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 47 publications
2
29
1
Order By: Relevance
“…Another group of SLE patients originated from a cross-sectional sub-cohort of the register designed to examine cardiovascular involvement (“SLE-VASK”) ( 23 ). These patients ( n =59) had ≥1 year’s duration of SLE and available data on the IGS.…”
Section: Methodsmentioning
confidence: 99%
“…Another group of SLE patients originated from a cross-sectional sub-cohort of the register designed to examine cardiovascular involvement (“SLE-VASK”) ( 23 ). These patients ( n =59) had ≥1 year’s duration of SLE and available data on the IGS.…”
Section: Methodsmentioning
confidence: 99%
“…The patients donated peripheral blood and the disease activity, defined by SLE disease activity index 2000 (SLEDAI-2K), was recorded from their closest regular visit to rheumatologist. All patients were considered to have low disease activity but could be serologically active and clinically quiescent at sampling ( 20 , 21 ). Each participant gave written informed consent, and the study protocol was approved by the regional ethics board in Linköping.…”
Section: Methodsmentioning
confidence: 99%
“…23 We have recently shown that an extended HFUS protocol focused on multiple arterial areas may provide the clinician with additional information on the vessel wall appearance, in SLE subjects. 24 We recorded that increased IMT (!0.9 mm) observed in SLE predominantly showed appearance of a medium echogenic, homogenous wall thickening that can be found in inflammatory vascular disease. Concerning early wall changes in SLE, our results indicated other potential mechanisms apart from atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning early wall changes in SLE, our results indicated other potential mechanisms apart from atherosclerosis. 24 Herein, we aimed to investigate the reliability of pOPN as a surrogate biomarker of atherosclerosis in the common carotid arteries (CCA) of subjects with different SLE phenotypes i.e. in patients with either APS, or nephritis (LN), or isolated skin/joint involvement, as well as in matched control subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation